Understanding Brexit : Why Britain Voted to Leave the European Union. - Taylor, Graham (SocietyNow., 2017)
On 23rd June 2016, the United Kingdom shocked the world by voting to leave the European Union. This short book examines why this happened, examining the historical, economic, political, social and cultural reasons that led to the Brexit vote.